-5(2-p)=6+3(p-2)

Simple and best practice solution for -5(2-p)=6+3(p-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2-p)=6+3(p-2) equation:



-5(2-p)=6+3(p-2)
We move all terms to the left:
-5(2-p)-(6+3(p-2))=0
We add all the numbers together, and all the variables
-5(-1p+2)-(6+3(p-2))=0
We multiply parentheses
5p-(6+3(p-2))-10=0
We calculate terms in parentheses: -(6+3(p-2)), so:
6+3(p-2)
determiningTheFunctionDomain 3(p-2)+6
We multiply parentheses
3p-6+6
We add all the numbers together, and all the variables
3p
Back to the equation:
-(3p)
We add all the numbers together, and all the variables
2p-10=0
We move all terms containing p to the left, all other terms to the right
2p=10
p=10/2
p=5

See similar equations:

| 45/16x=0 | | 63=3n+7(n-2) | | L=13x-3 | | (2/3)t+(13/5)=(22/3) | | -133=-19v | | 8(1+2t)= | | c+79/4=-5 | | 4b+44=180 | | p-3-3p=-1 | | v/4-10=10 | | 45×16x=0 | | 7d−12+3d=15 | | (v+3)(2)= | | 45-16x=0 | | 8=2m-2 | | 5(b+3)=-55 | | 9-7n=-5 | | 17=-7p=38 | | 40a2-32a=0 | | k+26/6=8 | | (4x-6)(2x+2)=(2x+3)(4x-4) | | 9r+2=92 | | 33/8+w=15/6 | | 8(y-10)=42 | | x-3/2+x+1/3=1 | | q+5/9=1/6. | | 7(w+4)=56 | | 3b+5=-18 | | s+33/4=61/8 | | -18+9u=27 | | 1/2=q+(2/3) | | 3t+120=180 |

Equations solver categories